2017
DOI: 10.1186/s12883-017-0987-y
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation is not uncommon among patients with ischemic stroke and transient ischemic stroke in China

Abstract: BackgroundAtrial fibrillation (AF) is reported to be a less frequent cause of ischemic stroke in China than in Europe and North America, but it is not clear whether this is due to underestimation. Our aim was to define the true frequency of AF-associated stroke, to determine the yield of 6-day Holter ECG to detect AF in Chinese stroke patients, and to elucidate predictors of newly detected AF.MethodsPatients with acute ischemic stroke or transient ischemic attack (TIA) were enrolled in a prospective, multicent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…The percentage of prior OAs use in this study was lower than a recent cohort study [ 14 ]. The underuse of warfarin [ 19 ]could be related to the underestimate of the risk of atrial fibrillation[ 20 ] and cost of oral non-vitamin K antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of prior OAs use in this study was lower than a recent cohort study [ 14 ]. The underuse of warfarin [ 19 ]could be related to the underestimate of the risk of atrial fibrillation[ 20 ] and cost of oral non-vitamin K antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…The detection model included demographics, medical history, anthropometrics, and conventional risk factors. However, the Framingham model overestimates the risk of stroke in China because of obvious differences in the disease spectrum and risk factors [17,18]. A joint Chinese-American research group constructed a risk detection model of ischemic stroke and hemorrhagic stroke with 6 risk factors, including systolic blood pressure, sex, age, total cholesterol (TC), diabetes, and smoking [19].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical information such as demographic information, stroke risk factors, detailed medical history, and treatments were assessed as previously described. [4]…”
Section: Methodsmentioning
confidence: 99%
“…[3] The China Atrial Fibrillation Screening in Acute Ischemic Stroke Patients (CRIST) trial, which recruited consecutive 1556 patients with ischemic and transient ischemic attack (TIA) within 7 days from October 2013 to June 2015, showed that prolonged monitoring evaluation (6 days) could increase AF detection to about 20% in China, of these 4.4% were newly detected AF. [4] However, the available evidence demonstrated no significant benefit of oral anticoagulation for stroke prevention in such patients. [57] Although AF is a well-known risk factor for cardioembolic stroke, it is not always directly responsible for the embolism.…”
Section: Introductionmentioning
confidence: 99%